Teaching Self-Determination Skills to Male Adolescents with Mild/Moderate Disabilities - Battles, Dawn; Pierson, Melinda R. (Journal of Gender and Power, 2019)
The importance of teaching self-determination skills to all students is extremely important, but it especially vital that all adolescent males learn these skills as they seem to struggle the most with self-advocacy, communication skills, and self-efficacy. This article will focus on many facets of self-determination and will present interventions specifically for adolescent males.